Understanding depression in type 2 diabetes: a biological approach in observational studies [version 1; referees: 2 approved] - Thomas van Sloten; Miranda Schram (F1000Research, 2018)
Depression is twice as common in type 2 diabetes as in the general population and is associated with adverse health outcomes. Growing evidence suggest that type 2 diabetes and depression share biological mechanisms. This brief commentary discusses current understanding of shared biological pathways, focussing on hyperglycaemia, (micro)vascular dysfunction, and low-grade inflammation. Although there is accumulating evidence that these pathways are involved in the link between type 2 diabetes and depression, direct evidence of their temporal associations is lacking because of a paucity of longitudinal studies that focus on the pathobiology of both type 2 diabetes and depression.